Respuesta :

gmany

[tex]\text{Use}\ a^n\cdot a^m=a^{n+m}\\\\-3d^8(-4d^{-14})=(-3)(-4)d^{8+(-14)}=12d^{-6}[/tex]

Answer:

[tex]12d^{-6}[/tex]

Step-by-step explanation:

The given expression is

[tex]-3d^{8}(-4d^{-14})[/tex]

To simplify this expression, we have to apply the exponent property which states that power with similar base can be simplified by adding their exponents. As it follows

[tex]-3d^{8}(-4d^{-14})=12d^{8-14}=12d^{-6}[/tex]

Therefore, the simplified expression is

[tex]12d^{-6}[/tex]

ACCESS MORE